RISK FACTORS FOR MENTAL DISORDERS IN THE WORKING AREA OF THE LIMBOTO HEALTH CENTER - Bolilio, Puput Kristian; Firmawati, Firmawati; I. Biahimo, Nur Uyuun (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2023)
Abstract: Genes contribute around 37 percent of the risk of developing mental disorders, compared to other factors because individuals who have family members who experience mental disorders have a higher tendency. The cause of the disorder can also be influenced by drug abuse and chronic disease. Drug abuse can have long-term consequences to serious mental disorders such as psychosis. The aim of this research is to identify genetic factors, drug abuse and chronic diseases with the occurrence of mental disorders in the Limboto Community Health Center Work Area. Quantitative research design with a cross sectional study approach, a population of 123 mental disorder patients, a sample size of 55 people using accidental sampling technique in this study. The research results showed that 43 respondents (78.2%) had a genetic history, 6 respondents (10.9%) had drug abuse, 17 respondents (30.9%) had a history of disease and 29 respondents (52%) had neuroses mental disorders. .7%). The results of the simple linear regression test showed that there was an influence of genetic factors (p=0.005), drug abuse (p=0.009) and history of illness (p=0.042) on the occurrence of mental disorders in the Limboto Health Center Working Area. It was concluded that genetic factors, drug abuse and a history of illness influence the occurrence of mental disorders Keywords : Mental Disorders, Genetics, Chronic Diseases, Drug Abuse